Non-Gaussian statistical communication theory - Middleton, David, 1920-; Wiley InterScience (Online service) (Hoboken, N.J. : Wiley-IEEE Press, 2012)
"The book is based on the observation that communication is the central operation of discovery in all the sciences. In its "active mode" we use it to "interrogate" the physical world, sending appropriate "signals" and receiving nature's "reply". In the "passive mode" we receive nature's signals directly. Since we never know a priori what particular return signal will be forthcoming, we must necessarily adopt a probabilistic model of communication"--
Reception as a Statistical Decision Problem -- Space-Time Covariances and Wave Number Frequency Spectra: I. Noise and Signals with Continuous and Discrete Sampling -- Optimum Detection, Space-Time Matched Filters, and Beam Forming in Gaussian Noise Fields -- Multiple Alternative Detection -- Bayes Extraction Systems: Signal Estimation and Analysis, () = 1 -- Joint Detection and Estimation, () = 1: I. Foundations -- Joint Detection and Estimation under Uncertainty, () <1. II. Multiple Hypotheses and Sequential Observations -- The Canonical Channel I: Scalar Field Propagation in a Deterministic Medium -- The Canonical Channel II: Scattering in Random Media; 'Classical' Operator Solutions.
Includes bibliographical references and index.
Print version record.
Keywords: Statistical communication theory; Information theory -- Statistical methods; Gaussian processes; SCIENCE -- Waves & Wave Mechanics; Gaussian processes; Information theory -- Statistical methods; Statistical communication theory; Electronic books